Starch in food : structure, function and applications - Eliasson, Ann-Charlotte, 1953- (Woodhead Publishing in food science and technology., 2004)
Starch is both a major component of plant foods and an important ingredient for the food industry. Starch in food reviews starch structure and functionality and the growing range of starch ingredients used to improve the nutritional and sensory quality of food. Part 1 illustrates how plant starch can be analysed and modified, with chapters on plant starch synthesis, starch bioengineering and starch-acting enzymes. Part 2 examines the sources of starch, from wheat and potato to rice, corn and tropical sources. The third part of the book looks at starch as an ingredient and how it is used in the food industry. There are chapters on modified starches and the stability of frozen foods, starch-lipid interactions and starch-based microencapsulation. Part 4 covers starch as a functional food, including the impact of starch on physical and mental performance, detecting nutritional starch fractions and analysing starch digestion.